Response of the nose to exercise in healthy subjects and in patients with rhinitis and asthma. Issue 2 (February 1994) - Serra-Batlles, J; Montserrat, J M; Mullol, J; Ballester, E; Xaubet, A; Picado, C
Abstract : BACKGROUND–Although the nose and the bronchi are both involved in the process of regulating respiratory heat exchange, thermal changes may precipitate airway obstruction during exercise but rarely cause nasal obstruction in patients with rhinitis. The cause of the different response of the nose and bronchial tree has hardly been investigated. This study was performed to assess the response of the nose during exercise in the presence of rhinitis, asthma, and in normal controls. METHODS–Ten healthy subjects (group 1), 15 patients with asthma and rhinitis (group 2), 10 with rhinitis only (group 3), and 11 with asthma only (group 4) were included in the study. Exercise was performed on a bicycle ergometer for six minutes, reaching a heart rate of 80% of predicted. Bronchial and nasal responses were measured by forced expiratory volume in one second (FEV1) and posterior rhinomanometry, respectively. A drop in the FEV1 of 20% or more was considered a positive exercise induced asthma challenge test. RESULTS–Heart rate and ventilation increased by a similar proportion in the four groups. The FEV1 significantly decreased in asthmatic patients (groups 2 and 4) but it did not change in healthy subjects (group 1) or in those with rhinitis (group 3). Thirteen asthmatic patients developed exercise induced asthma. Nasal patency increased with exercise by a similar proportion in all groups, and no differences were detected between those with rhinitis (groups 2 and 3) and those without (groups 1 and 4). Nasal patency had returned to basal values at 25 minutes after completion of exercise in the four groups. The nose of patients with exercise induced asthma, however, remained significantly more patent than in patients without exercise induced asthma between 10 and 30 minutes after exercise. CONCLUSIONS–These results suggest that the nose responds differently from the bronchi during exercise induced airway obstruction: whereas the bronchial tree responds by becoming narrowed, the nose becomes more patent. These findings suggest that the mechanisms regulating the response of the nose to exercise are different from those involved in the response of the bronchial tree.